Production Of Crude Aspergillus Fermentation Extract To Enhance The Quality Of Feed As A Productivity Booster Of Super Chicken - Aris Munandar; Vembriarto Jati Pramono (Jurnal Sain Veteriner, 2014)
Chicken meat is one of the most popular products that is really interesting for the consumers.The aim of this study was to produce feed supplement that can be used to improve food digestibility and productivity as well in local super chicken. In this research, Group I (control group) was given feed and drink. ad libitum , Group II was given feed and drink ad libitum with the addition of fermented Aspergillus niger a dose of 4 ml / L of drinkingwater. Group III was given feed and drink ad libitum with the addition of fermented Aspergillus oryzae a dose of 4 ml / L of drinking water for 60 days, and then weight gain, food conversion rate as well as calcium and phosphate levels in the blood were observed. The results were analyzed using analysis of variance and showed that there were weight gain differences between the control and treatment groups of A. niger. There is no weight gain difference between the control and feed supplement groups . The blood calcium and phosphate levelsbetween the control and feed supplement groups were also not different.